Landscapes of housing design and planning in the history of environmental thought - Haffner, Jeanne, 1973-. (London ;New York Routledge, Taylor & Francis Group, 2022)
"In the twenty-first century, housing has become a site of ecological experimentation and environmental remediation. From the vantage point of contemporary architecture, conservation concerns and emergent building science technologies support one another, with new processes and materials deployed to reduce energy usage, water consumption, and CO2 emissions. Landscapes of Housing examines this trend in historical perspective, arguing for a more considered environmental vision that includes the organic, social, and cultural dimensions of landscape. By shifting the focus from architecture, the book highlights and critiques the relationship between dwelling and landscape itself. Contributors from a wide range of international perspectives propose a more integrative ecology that includes history, culture, society, and materiality, in addition to technology, within contemporary ecological housing programs. This book will be a resource for upper-level students, academics, and researchers in landscape architecture interested in the social and political implications of ecological housing".
Includes bibliographical references and index.
Keywords: Housing -- History; Housing -- Environmental aspects -- History; Housing policy -- Social aspects -- History